Childhood Medulloblastoma: Current Therapies, Emerging Molecular Landscape and Newer Therapeutic Insights - Khatua, Soumen; Song, Anne; Sridhar, Divyaswathi C.; Mack, Stephen C. (Current Neuropharmacology, 2018)
Background: Medulloblastoma is the most common malignant brain tumor in children, currently treated uniformly based on histopathology and clinico-radiological risk stratification leading to unpredictable relapses and therapeutic failures. Identification of molecular subgroups have thrown light on the reasons for these and now reveals clues to profile molecularly based personalized therapy against these tumors. Methods: Research and online contents were evaluated for pediatric medulloblastoma which included latest information on the molecular subgroups and their clinical relevance and update on efforts to translate them into clinics. Results: Scientific endeavors over the last decade have clearly identified four molecular variants (WNT, SHH, Group 3, and Group 4) and their demographic, genomic, and epigenetic profile. Latest revelations include significant heterogeneity within these subgroups and 12 different subtypes of MB are now identified with disparate outcomes and biology. These findings have important implications for stratification and profiling future clinical trials against these formidable tumors. Conclusion: With the continued outpouring of genomic/epigenomic data of these molecular subgroups and evolution of further subtypes in each subgroup, the challenge lies in comprehensive evaluation of these informations. Current and future endeavors are now needed to profile personalized therapy for each child based on the molecular risk stratification of medulloblastoma, with a hope to improve survival outcome and reduce relapses.
Keywords: epigenetic machinery